Registration of 'Ho 07‐613' sugarcane. Issue 2 (23rd April 2022) - Hale, Anna L.; Todd, James; Pan, Yong‐Bao; Tew, Thomas L.; Veremis, John C.; White, William; Dufrene, Edwis O.; Grisham, Michael P.; Gravois, Kenneth A.; Jackson, Windell; Dalley, Caleb D.; Spaunhorst, Douglas; et al.
Abstract: 'Ho 07‐613' (Reg. no. CV‐208, PI 699606) sugarcane (an interspecific hybrid of Saccharum officinarum L., S. barberi Jeswiet, S. spontaneum L., and S. sinense Roxb. amend. Jeswiet) was selected and evaluated by scientists at the USDA‐ARS, working cooperatively with the Louisiana State University Agricultural Center and the American Sugar Cane League, Inc. It was released to growers in Louisiana in 2014. The cultivar was tested across the crop cycle (plant cane and first and second ratoon) at 12 farm locations and compared with 'HoCP 96‐540', the most widely grown cultivar in Louisiana during that time. The plant‐cane sucrose yield (Mg ha –1 ) of Ho 07‐613 was equivalent to HoCP 96‐540, and sucrose content was significantly higher. Ho 07‐613 has moderately early maturity and poor mature‐stalk cold tolerance. The cultivar is resistant to smut and Sorghum mosaic virus, tolerant of ratoon stunt, and moderately resistant to brown rust and leaf scald. It is moderately resistant to the sugarcane borer, Diatraea saccharalis (F.), and moderately responsive to glyphosate ripener. Ho 07‐613's high yield potential, low fiber, and disease resistance make it a useful addition to existing commercial sugarcane cultivars in Louisiana.